Cumulative neonatal oxygen exposure predicts response of adult mice infected with influenza A virus. Issue 3 (22nd May 2014) - Maduekwe, Echezona T.; Buczynski, Bradley W.; Yee, Min; Rangasamy, Tiruamalai; Stevens, Timothy P.; Lawrence, B. Paige; O'Reilly, Michael A.
Summary An acceptable level of oxygen exposure in preterm infants that maximizes efficacy and minimizes harm has yet to be determined. Quantifying oxygen exposure as an area‐under‐the curve (OAUC) has been predictive of later respiratory symptoms among former low birth weight infants. Here, we test the hypothesis that quantifying OAUC in newborn mice can predict their risk for altered lung development and respiratory viral infections as adults. Newborn mice were exposed to room air or a FiO2 of 100% oxygen for 4 days, 60% oxygen for 8 days, or 40% oxygen for 16 days (same cumulative dose of excess oxygen). At 8 weeks of age, mice were infected intranasally with a non‐lethal dose of influenza A virus. Adult mice exposed to 100% oxygen for 4 days or 60% oxygen for 8 days exhibited alveolar simplification and altered elastin deposition compared to siblings birthed into room air, as well as increased inflammation and fibrotic lung disease following viral infection. These changes were not observed in mice exposed to 40% oxygen for 16 days. Our findings in mice support the concept that quantifying OAUC over a currently unspecified threshold can predict human risk for respiratory morbidity later in life. Pediatr Pulmonol. 2015; 50:222–230. © 2014 Wiley Periodicals, Inc.